Adaptive Control Strategy for Real-Time Regulation of PEV Charging in Response to Fluctuating Renewable Energy Supply - Jayasri Nemala; Devi V.S. Anusuya; Tewari Preeti; Lakhanpal Sorabh; Abedi Tamam Ali Abd Ulabbas; Bodha Kapil (E3S Web of Conferences)
This study is concerned with the coordinated charging pattern of plugin electric vehicles (PEVs) by using a simulation and control framework. The first of these is to develop a novel control technique based on a grid structure to manage the charging power of PEVs in reaction to fluctuating renewable energy sources. The grid is assumed to control and communicate instantly and directly through a common control signal the electricity used for PEV charging. Based on the principle of market-based demand modeling, the subsequent theoretical formulation involves a system of partial differential equations for concurrent PEV charging. It is then applied to future real world driving data and compared to a PEV Monte Carlo model. Moreover, the principles of SM control are introduced to synthesize the robust output feedback controller for the system without state error. The fluctuating PEV count is addressed by focusing on the sole observable output: the instantaneous mismatch of supply and demand of renewable electricity by customers. The performance of the controller is evaluated in the present research based on a real wind power state trajectory through numerical simulations of the system.